A STUDY ON PREVALENCE OF DIABETES MELLITUS TYPE 2 AMONG PATIENTS AGED 30-60 YEARS ATTENDING HEALTH SERVICE AT BUKEDEA HEALTH CENTER IV IN BUKEDEA DISTRICT. A CROSS-SECTIONAL STUDY. - Otigo , William; Kiyingi , Daisy (Student’s Journal of Health Research Africa, 2023)
Background: Type2 diabetes mellitus is a type of diabetes mellitus that is very prevalent in Uganda and affects a wide percentage of the adult population. Much as there have been successive Interventions in the prevention and control of this non-communicable disease, it’s still increasing annually. The purpose of the study: The study was conducted to find out the prevalence of diabetes mellitus type 2 among clients 30-60 years at Bukedea Health center IV. Study objectives: The study objectives were; Prevalence, individual factors and knowledge of patients on diabetes mellitus type 2 among adult clients between age30-60 years. Methodology: A cross sectional study of 80 respondents was used for the study. A simple random sampling technique was used and data collected using survey and interviewing method was presented and analyzed using descriptive frequencies and percentages using Microsoft Excel and Microsoft word. Results: There is slightly high prevalence of diabetes mellitus type 2 with 38 (47%) having been diagnosed with the condition, 28 (38%) having a family member diagnosed with the condition and 9 (11%) having their sugar levels above 10mm/l, the majority of respondents 68 (85%) were ignorant about the condition, 12 (15%) were weighing above 60kgs ,majority 50 (62%) had gained weight and of which the majority 57 (71%) do not do body exercise, The conclusions: Of the 80 respondents, few had their sugar levels above 10 mm/l, still many had ever been diagnosed with diabetes mellitus. and had a family member diagnosed with diabetes mellitus 2,slightly a moderate number of patients had no knowledge about diabetes mellitus, while still a slight majority were weighing above 60 kgs, However a majority of the respondents had gained weight, majority of respondents still don’t do body exercise.